2015
DOI: 10.4085/1062-6050-49.3.59
|View full text |Cite
|
Sign up to set email alerts
|

Career and Family Aspirations of Female Athletic Trainers Employed in the National Collegiate Athletic Association Division I Setting

Abstract: Context: Female athletic trainers (ATs) tend to depart the profession of athletic training after the age of 30. Factors influencing departure are theoretical. Professional demands, particularly at the collegiate level, have also been at the forefront of anecdotal discussion on departure factors.Objective: To understand the career and family intentions of female ATs employed in the collegiate setting.Design: Qualitative study. Setting: National Collegiate Athletic Association Division I. Patients or Other Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…27 Regardless of their role in the collegiate setting, ATs experience challenges with work-life balance, which can affect career planning. 15 Career advancement in athletic training has been linked to parenting. 15 In fact, motherhood has been documented as a primary barrier to women assuming leadership positions, particularly the head AT role, in collegiate athletics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Regardless of their role in the collegiate setting, ATs experience challenges with work-life balance, which can affect career planning. 15 Career advancement in athletic training has been linked to parenting. 15 In fact, motherhood has been documented as a primary barrier to women assuming leadership positions, particularly the head AT role, in collegiate athletics.…”
Section: Discussionmentioning
confidence: 99%
“…The second set of questions was open ended and focused on participants' experiences as mothers, ATs, and leaders or managers. The questions were derived from the previous literature 15 and our intended purpose of the study. We also borrowed questions from Mazerolle et al, 16 who investigated the experiences of female head ATs in the Division I setting (Appendix).…”
Section: Data-collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Athletic trainers, especially those in the largest setting, college, 16 often work long hours (60þ per week), accompanied by required travel and often minimal control over their weekly work schedule. [17][18][19][20] These factors are organizational in nature and have been linked to experiences of burnout among ATs. 7,14 The time-intensive nature of the profession coupled with the demands of the work setting 4,7,19,21 inherently provide the platform for increased susceptibility to burnout.…”
mentioning
confidence: 99%
“…[17][18][19][20] These factors are organizational in nature and have been linked to experiences of burnout among ATs. 7,14 The time-intensive nature of the profession coupled with the demands of the work setting 4,7,19,21 inherently provide the platform for increased susceptibility to burnout. Interestingly, however, in a recent publication, Naugle et al 9 observed that despite working more hours, male ATs reported lower levels of burnout compared with female ATs.…”
mentioning
confidence: 99%